Benchmark for Synthesized Diamond Sensors Based on Isotopically Engineered Nitrogen‐Vacancy Spin Ensembles for Magnetometry Applications. Issue 9 (28th August 2020) - Osterkamp, Christian; Balasubramanian, Priyadharshini; Wolff, Gerhard; Teraji, Tokuyuki; Nesladek, Milos; Jelezko, Fedor
Abstract: Nitrogen‐vacancy (NV) center ensemble in synthetic diamond is a promising and emerging platform for quantum sensing technologies. Realization of such a solid‐state based quantum sensor is widely studied and requires reproducible manufacturing of NV centers with controlled spin properties, including the spin bath environment within the diamond crystal. Here, a non‐invasive method is reported to benchmark NV ensembles regarding their suitability as ultra‐sensitive magnetic field sensors. Imaging and electron spin resonance techniques are presented to determine operating figures and precisely define the optimal material for NV‐driven diamond engineering. The functionality of the methods is manifested on examples of chemical vapor deposition synthesized diamond layers containing preferentially aligned, isotopically controlled 15 NV center ensembles. Quantification of the limiting 15 N P1 spin bath, in an otherwise 12 C enriched environment, and the reduction of its influence by applying dynamical decoupling protocols, complete the suggested set of criteria for the analysis of NV ensemble with potential use as magnetometers. Abstract : Nitrogen‐vacancy (NV) center ensembles represent solid‐state qubits with possible applications as quantum sensors. Controlling the nitrogen content in nanometer‐scale diamond layers and analyzing the ratio between the sensor (NVs) and noise bath spins (P1 centers) by using the sensing capabilities of the sensor itself, enable the benchmarking and tuning of several production approaches to identify superior growth and sensor fabrication strategies.